Stock Picking and Market Timing of the Egyptian Fund Managers: Evidence from the Financial Crisis - Elmesseary, Mohammad (European Journal of Sustainable Development, 2014)
The findings of over-or-under performance of fund managers across the crisis periods are mixed. By analyzing the data of 35 Egyptian funds, this paper investigates the two skills of market timing and selectivity during-and-post the 2007-2008 financial turmoil; it also examines the comparative performance between the conventionaland Islamic mutual funds. The results show no evidence of these skills even for the overall period or for the crisis one, where Chow – test documents that there are no structural changes either for the regression line or for its coefficients across the two sub-periods. These findings are supported by using a well-known benchmark. Thus, it seems that investors cannot gain superior returns by investing in the mutual funds industry as a whole. Furthermore, the outcomes of the cross-sectional analysis report that investors cannot also attain higher returns by investing in a particular fund group against the other, implying that the ethical screening, which is adopted by the Islamic ones, and which limits their potentials of diversification does not impact their performance. JEL classification: G1; G2 Keywords: Capital markets, Islamic mutual funds, performance evaluation, market timing ability, stock picking ability